Teknologi Produksi Benih Kentang untuk Mewujudkan Kemandirian Benih di BUMDes Desa Batur - Dr. Syarif Husen; Agus Eko Purnomo; Aniek Iriany; Muhidin Muhidin; Aulia Zakia; Iqbal Ramadhani Fuadiputra; M. Zul Mazwan; Farusa Anggita; Rizka Nurfitriani (Institut Pertanian Bogor, 2024)
The area at the foot of Mount Merbabu, more precisely in Batur Village, has an altitude of 1,200‒1,800 meters above sea level, so it is very suitable for cultivating potato plants. Several farmers have cultivated this, but the production results are not always optimal. The potato crop productivity problems faced by farmers in BUMDes are: 1) Limited quality seeds; 2) The price of seeds is high and difficult for farmers to reach; 3) Farmers use seeds from some crops that are not of good quality so the yield is low and susceptible to disease; and 4) Farmers are unfamiliar with the technology for producing superior potato seeds. The University of Muhammadiyah Malang has superior virus-free seed sources and technology that can be adopted and disseminated to farmers to produce quality seeds independently so that they can overcome the problems they face. Activities are carried out in a participatory manner using tutorial methods, training and demonstration plots at locations, and group mentoring. Partners agree to actively provide human resources, necessary facilities, and accompanying funds in implementing activities. At this time, farmers have understood planet acclimatization technology. They can produce 5,000 mini cuttings from 500 acclimatized broodstock, 10,000 G0 seeds, and 25 tonnes/ha of G2 seeds using rooted shoot-cutting technology. Additionally, partner farmers have obtained permits as seed producers from BPSB (Seed Supervision and Certification Center). This program is ongoing, and UMM will assist on an ongoing basis until the establishment of an independent BUMDes for potato seeds in Semarang Regency.